# 2006 AIME II Problems/Problem 15

## Problem

Given that $x, y,$ and $z$ are real numbers that satisfy: $x = \sqrt{y^2-\frac{1}{16}}+\sqrt{z^2-\frac{1}{16}}$ $y = \sqrt{z^2-\frac{1}{25}}+\sqrt{x^2-\frac{1}{25}}$ $z = \sqrt{x^2 - \frac 1{36}}+\sqrt{y^2-\frac 1{36}}$

and that $x+y+z = \frac{m}{\sqrt{n}},$ where $m$ and $n$ are positive integers and $n$ is not divisible by the square of any prime, find $m+n.$

## Solution 1 (Geometric Interpretation)

Let $\triangle XYZ$ be a triangle with sides of length $x, y$ and $z$, and suppose this triangle is acute (so all altitudes are in the interior of the triangle).

Let the altitude to the side of length $x$ be of length $h_x$, and similarly for $y$ and $z$. Then we have by two applications of the Pythagorean Theorem we that $$x = \sqrt{y^2 - h_x^2} + \sqrt{z^2 - h_x^2}$$ As a function of $h_x$, the RHS of this equation is strictly decreasing, so it takes each value in its range exactly once. Thus we must have that $h_x^2 = \frac1{16}$ and so $h_x = \frac{1}4$ and similarly $h_y = \frac15$ and $h_z = \frac16$.

The area of the triangle must be the same no matter how we measure it; therefore $x\cdot h_x = y\cdot h_y = z \cdot h_z$ gives us $\frac x4 = \frac y5 = \frac z6 = 2A$ and $x = 8A, y = 10A$ and $z = 12A$.

The semiperimeter of the triangle is $s = \frac{8A + 10A + 12A}{2} = 15A$ so by Heron's formula we have $$A = \sqrt{15A \cdot 7A \cdot 5A \cdot 3A} = 15A^2\sqrt{7}$$

Thus, $A = \frac{1}{15\sqrt{7}}$ and $x + y + z = 30A = \frac2{\sqrt{7}}$ and the answer is $2 + 7 = \boxed{9}$.

The justification that there is an acute triangle with sides of length $x, y$ and $z$:

Note that $x, y$ and $z$ are each the sum of two positive square roots of real numbers, so $x, y, z \geq 0$. (Recall that, by AIME convention, all numbers (including square roots) are taken to be real unless otherwise indicated.)

Also, $\sqrt{y^2-\frac{1}{16}} < \sqrt{y^2} = y$, so we have $x < y + z$, $y < z + x$ and $z < x + y$. But these conditions are exactly those of the triangle inequality, so there does exist such a triangle.

## Solution 2 (Algebraic)

Note that none of $x,y,z$ can be zero.

Each of the equations is in the form $$a=\sqrt{b^2-d^2}+\sqrt{c^2-d^2}$$

Isolate a radical and square the equation to get $$b^2-d^2=a^2-2a\sqrt{c^2-d^2}+c^2-d^2$$

Now cancel, and again isolate the radical, and square the equation to get $$a^4+b^4+c^4+2a^2c^2-2a^2b^2-2b^2c^2=4a^2c^2-4a^2d^2$$

Rearranging gives $$a^4+b^4+c^4=2a^2b^2+2a^2c^2+2b^2c^2-4a^2d^2$$

Now note that everything is cyclic but the last term (i.e. $-4a^2d^2$), which implies $$-4x^2\cdot\frac1{16}=-4y^2\cdot\frac1{25}=-4z^2\cdot\frac1{36}$$

Or $$x: y: z=4: 5: 6 \implies x=\frac{4y}5 \textrm{ and } z=\frac{6y}5$$

Plug these values into the middle equation to get $$\frac{256y^4+625y^4+1296y^4}{625}=\frac{800y^4}{625}+\frac{1800y^4}{625}+\frac{1152y^4}{625}-\frac{100y^2}{625}$$

Simplifying gives $$1575y^4=100y^2 \textrm{ but } y \neq 0 \implies y^2=\frac4{63} \textrm{ or } y=\frac2{3\sqrt7}$$

Substituting the value of $y$ for $x$ and $z$ gives $$x+y+z = \frac{4y+5y+6y}5 = 3y = 3 \cdot \frac{2}{3\sqrt7} = \frac{2}{\sqrt7}$$

And thus the answer is $\boxed{009}$

~phoenixfire

## Video solution

The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions. 